2021
DOI: 10.4315/jfp-20-417
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Closely Related Listeria monocytogenes Isolates with No Apparent Evidence for a Common Source or Location: A Retrospective Whole Genome Sequencing Analysis

Abstract: Public health and regulatory agencies worldwide sequence all Listeria monocytogenes (Lm) isolates obtained as part of routine surveillance and outbreak investigations. Many of these entities submit the sequences to the NCBI Pathogen Detection (NCBI PD) database, which groups the Lm isolates into SNP clusters based on a pairwise SNP difference threshold of 50 SNPs. Our goal was to assess if isolates with metadata suggesting different sources or locations could show evidence for close genetic relatedness indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The increased number of accessory genes (around 80% of the pan genome) is responsible for most of the strain-specific features even when variation in core virulence genes is present. Several studies have shown that isolates belonging to the same genotypic subgroup (CC/ST) often share the same virulence genes no matter the source of isolation [ 1 , 6 , 56 ] as shown in Figure 2 and Figure 3 . Furthermore, while there is a differential distribution of CC/STs in human-associated and ruminant-associated isolates, major CCs such as CC1 and CC4 have been shown to spread globally causing most of the listeriosis cases in both hosts [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased number of accessory genes (around 80% of the pan genome) is responsible for most of the strain-specific features even when variation in core virulence genes is present. Several studies have shown that isolates belonging to the same genotypic subgroup (CC/ST) often share the same virulence genes no matter the source of isolation [ 1 , 6 , 56 ] as shown in Figure 2 and Figure 3 . Furthermore, while there is a differential distribution of CC/STs in human-associated and ruminant-associated isolates, major CCs such as CC1 and CC4 have been shown to spread globally causing most of the listeriosis cases in both hosts [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These and other results show that NGS technology, due to its highthroughput capability and the development of new bioinformatics tools to analyze the obtained sequence data, is the most specific molecular tool for subtyping of microorganisms, including L. monocytogenes (Hurley et al, 2019;Jagadeesan, Baert, et al, 2019;Lachtara et al, 2021;Lüth et al, 2018Lüth et al, , 2021Moura et al, 2017;Orsi et al, 2021).…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 75%
“…Furthermore, thanks to the cgMLST analysis, the human cases could be traced back and the source of L. monocytogenes responsible for the outbreak was identified (Kleta et al., 2017 ). These and other results show that NGS technology, due to its high‐throughput capability and the development of new bioinformatics tools to analyze the obtained sequence data, is the most specific molecular tool for subtyping of microorganisms, including L. monocytogenes (Hurley et al., 2019 ; Jagadeesan, Baert, et al., 2019 ; Lachtara et al., 2021 ; Lüth et al., 2018 , 2021 ; Moura et al., 2017 ; Orsi et al., 2021 ).…”
Section: Molecular Typingmentioning
confidence: 94%
“…Recent application of whole-genome sequencing (WGS) into bacterial molecular characterization provides much data on the relationship of L. monocytogenes from different sources and allows the classification of the strains into evolutionary lines and genetic types [ 15 , 16 , 17 ]. Based on the WGS, the multilocus sequence typing (MLST) approach allows classification of L. monocytogenes into clonal complexes (CCs) and sequence types (STs), which are linked with persistence of the strains in food, food production environments or with a high potential to cause listeriosis [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that L. monocytogenes of CC121 classified as serogroup IIa has been often isolated from different food processing plants for several years, which makes them serious problems for the food industry and poses a potential threat for consumers [ 20 ]. Other data also suggest that L. monocytogenes IIa serogroup, classified to CC8, CC155, and other clonal complexes, have persistent properties and have been identified in different niches or sources [ 15 , 17 , 18 ]. WGS data also provides an opportunity to characterize L. monocytogenes based on the core genome multilocus sequence typing (cgMLST) that allows a standardized comparison of the sequences of the tested strains with the publicly available genomes present in databases [ 11 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%